From Patient to Provider: How Personal Medical Trauma Can Inform Supervision and Clinical Practice. (2nd October 2022) - Gordon, Robert M.; Grillo, Aria B.; Bernal-Fernandez, Natalia S.; Groth, Taylor D.; McGiffin, Jed N.; Hartline, Kenneth D.
ABSTRACT: Two predoctoral psychology interns share their personal reflections of neurological injuries they experienced during their adolescence and how it has informed and shaped their clinical work. Through their reflections, they provide insights and lessons learned as they have the unique first-hand experience of being a patient and now a rehabilitation psychology trainee and provider. Additionally, they describe how they have applied such knowledge during their clinical work with clients experiencing neurological and chronic health conditions. Issues involving communication with clients, families, and the treatment teams, the benefits and risks of self-disclosure, and the role of hope, meaning in life, and spirituality are discussed. The clinical practice implications of these insights are invaluable for trainees and healthcare specialists at all levels of experience, including the crucial role of supervision during the predoctoral internship year. Recommendations are made for clinical practice including providing developmentally appropriate communication and promoting an environment for growth and recovery. The authors are hopeful that the reflections provided in this article can inspire other trainees to feel comfortable in sharing their personal medical and psychological challenges as appropriate and relevant to help integrate their professional development.